Pengaruh Teamwork dan Fasilitas Kerja Terhadap Kepuasan Kerja Pegawai di UPTD Puskesmas Pesantren II Kota Kediri - Hanny Susiana Dewi; Erwin Syahputra; Anita Sumelvia Dewi (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to explain the significant influence between Teamwork and Work Facilities on Employee Job Satisfaction at UPTD Public Health Center Pesantren II Kediri City. The sample in this study was 40 respondents with a sampling method using purposive sampling in which the determination of the number of samples was based on certain criteria, namely civil servants. The data analysis technique used in this research is instrument test of validity and reliability, multiple linear regression test, classical assumption test and partial hypothesis test tested by t test while the simultaneous hypothesis is tested by F test. The results of the study show that Teamwork partially has a significant effect. on Employee Job Satisfaction and Work Facilities partially have a significant effect on Employee Job Satisfaction at UPTD Public Health Center Pesantren II Kediri City. Teamwork and work facilities simultaneously have a significant effect on employee job satisfaction at the UPTD Public Health Center Pesantren II Kediri City. In addition, the coefficient of determination (R2) of 0.503 or 50.3% is also obtained. This indicates that the Job Satisfaction of the UPTD Public Health Center of Pesantren II Kediri City is influenced by the Teamwork and Work Facilities variables by 50.3%. While the rest is influenced by other independent variables that are not included in this research model, which is 49.7%.